Hybridization Of Some Citrus Rootstock And Selection Of Tolerant Seedlings For Cold Stress - خوجه حسان; الخطيب علي; حسن فينوس (Latakia University Journal -Biological Sciences Series, 2021)
This study was carried out at the Agricultural Scientific Research Center in Lattakia, during the years 2018-2020, where the hybrid sons (resulting from a zygote) were selected on the basis of the morphological specifications of the citrus rootstocks within three groups as follows: The first group resulted from hybridization between (seed parent) Poncirus trifoliata (L.) Raf., (pollen parent) Citrus aurantium L., and the second group resulted from hybridization between (seed parent). Citrus reticulata Blanco, (pollen parent) Citrus aurantium L., and the third group resulted from hybridization between (seed parent) Citrus aurantium L., (pollen parent) Poncirus trifoliata (L.) Raf. Then these selected seedlings were exposed to one year age to (0)°C and ( 10-)°C , for a period of twenty-four hours, and the degree of damage to the seedlings was estimated in terms of survival, and the damage rate on the leaves, and the accumulation of proline was used as a chemical indication of the extent of the seedlings tolerance to cold stress. The accumulated proline in the leaves was calculated after the cold stress. The most important results indicated that citrus hybrids accumulated proline in the leaves upon stress, and this increased accumulation with increased stress and low temperature, where it was greater at stress (-10°C) than in (0)°C, and leaf tissues were exposed to damage after exposure to cold stress (-10°C) followed by complete drying of plants that survived only Four hybrids in the following spring, as the plants recovered for their physiological and biological activities and vegetative growth, while the hybrids were not affected to (0) C and there was no damage to leaf tissue.